Delayed exposure to environmental enrichment improves functional outcome after stroke - Ying Tang; Ming-Yue Li; Xin Zhang; Xing Jin; Jing Liu; Ping-He Wei (Elsevier, 2019)
Stroke is one of the leading causes of long-term disabilities worldwide. Although exposure to an enriched environment (EE) initiated in the acute phase after stroke has neuroprotective effects and improves stroke outcome, it remains unclear whether EE has positive effects when started in a delayed time frame. Here we show that exposure to EE in the delayed phase notably ameliorates the ischemia-induced impairments in neurological functions and spatial learning and memory. In addition, delayed EE exposure after stroke significantly promotes the survival and neuronal fate choice of hippocampal newborn cells, increases synaptic density of hippocampal mature neurons, and enhances the migration of subventricular zone (SVZ)-derived cells towards the ischemic striatum. Histone deacetylase 2 (HDAC2), synapse-associated proteins and brain-derived neurotrophic factor (BDNF) may respectively mediate these roles of delayed EE. Our findings provide the suggestion that exposure to EE initiated in the delayed phase after stroke promotes plastic changes via affecting neurogenesis, synaptogenesis and neuronal migration, and thus improves stroke outcome. Because EE initiated earlier than 24 h is clinically feasible, our work could be introduced into clinical studies of stroke directly and may provide stroke survivors with a new strategy for their functional recovery. Keywords: Stroke, Enriched environment, Neurogenesis, Synaptogenesis, Neuronal migration